Local Grain Growth in Cemented Carbide Sintering - Alizadeh, E. (Asian Journal of Chemistry, 2010)
Two possible origins for local grain growth during sintering of fine WC-Co grades have been investigated. The main origin for formation of big WC crystals in a fine WC-Co structure is the presence of big WC seed crystals or particles, already contained in WC powder, which at least partially survived WC+Co lling. Growing mechanism during sintering is Ostwald ripening. Another possible reason is the presence of heterogeneous impurities which locally form low melting alloys with the cobalt binder, thus enabling dissolution and crystallization of WC in that area much earlier than for bulk material. Contrary to many researchers' assumptions, no influence of carbon heterogeneities was found.